Kajian Standar Pelayanan Minimal Jalan Provinsi DIY Pendukung Aksesibilitas Kawasan Pantai Selatan Gunungkidul - Yohanes Wira Sasongko Putro (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
Visitors to the southern coast of Gunungkidul tend to increase every year. The Gading – Saptosari and Wonosari – Baron routes need to be supported by transportation infrastructure that complies with the Road Minimum Service Standards (MSS). After analyzing the performance of the existing road sections and the next 10 years by considering the growth rate of vehicles and the increase in tourist visits, an evaluation of the fulfillment of Road MSS criteria is carried out. Furthermore, recommendations to improve the performance of road sections to meet the standards are analyzed. The existing degree of saturation on both routes is still <0.85, but only the Paliyan – Saptosari section meets the requirements in 2032 for all growth rates. None of the segments met all the MSS criteria evaluated in this study. The alternative of widening the road towards the primary collector standard with land optimization shows a significant increase in performance in 2032. Widening the road and shoulders towards compliance with the MSS does not provide a significant increase compared to the first alternative.